Integrated transcriptomic and proteomic analyses reveal ɑ‐lipoic acid‐regulated cell proliferation via Grb2‐mediated signalling in hepatic cancer cells. Issue 6 (25th March 2018) - Yang, Lan; Wang, Xiliang; Xu, Juan; Wen, Ya; Zhang, Manqiao; Lu, Jingxiao; Wang, Rongfu; Sun, Xiaojuan
Abstract: Hepatocellular carcinoma is the most frequent primary liver cancer worldwide. The use of antioxidants as cancer prevention and treatment agents has become a focus of research in recent years due to their limited adverse effects. Alpha lipoic acid (ɑ‐LA) is synthesized in the liver and is considered a naturally occurring antioxidant. In this study, a total of 4446 differentially expressed genes (2097 down‐regulated and 2349 up‐regulated) were identified via RNA‐Seq in HepG2 cells after exposure to α‐LA for 24 hrs. Moreover, GO and KEGG pathway analyses showed that cancer‐relevant cell membrane proteins were significantly affected. An interaction network analysis predicted that Grb2 might mediate the key target pathways activated by exposure to ɑ‐LA. Verification of the RNA‐Seq and iTRAQ results confirmed that Grb2 mediated the ɑ‐LA‐induced inhibition of cell proliferation in vitro . Furthermore, the analysis of human hepatocellular carcinoma specimens obtained from the GEO database showed that the expression of EGFR and Met correlated with that of Grb2. These findings provide a novel mechanism through which ɑ‐LA regulates cell proliferation via the down‐regulation of growth factor‐stimulated Grb2 signalling.